Case report: A case study of variant calling pipeline selection effect on the molecular diagnostics outcome - Skitchenko, Rostislav; Smirnov, Sergey; Krapivin, Mikhail; Smirnova, Anna; Artomov, Mykyta; Loboda, Alexander; Dinikina, Yulia (Frontiers in Oncology, 2024)
Next-generation sequencing technologies have not only defined a breakthrough in medical genetics, but also been able to enter routine clinical practice to determine individual genetic susceptibilities. Modern technological developments are routinely introduced to genetic analysis overtaking the established approaches, potentially raising a number of challenges. To what extent is the advantage of new methodologies in synthetic metrics, such as precision and recall, more important than stability and reproducibility? Could differences in the technical protocol for calling variants be crucial to the diagnosis and, by extension, the patient’s treatment strategy? A regulatory review process may delay the incorporation of potentially beneficial technologies, resulting in missed opportunities to make the right medical decisions. On the other hand, a blind adoption of new technologies based solely on synthetic metrics of precision and recall can lead to incorrect conclusions and adverse outcomes for the specific patient. Here, we use the example of a patient with a WHO-diagnosed desmoplastic/nodular SHH-medulloblastoma to explore how the choice of DNA variant search protocol affects the genetic diagnostics outcome.